9(u+2)=27

Simple and best practice solution for 9(u+2)=27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(u+2)=27 equation:



9(u+2)=27
We move all terms to the left:
9(u+2)-(27)=0
We multiply parentheses
9u+18-27=0
We add all the numbers together, and all the variables
9u-9=0
We move all terms containing u to the left, all other terms to the right
9u=9
u=9/9
u=1

See similar equations:

| 3÷4d+1÷5d+5d=d | | 3(q-4)=24 | | 3÷4+1÷5+5=d | | 2(e+5)=20 | | 78-2x=6 | | 0.25^x=16 | | y/3+1=6/y | | 3(x+2=11 | | 2h-2=16 | | 2(3x-1)=5x-5 | | 3^x+3-3^x+1=24 | | x(x+3)+5(x+3)=x+3x+5x+15 | | 2x+3*2^(x+1)=28 | | 2x+3*2^x+1=28 | | 7-2xx=-3 | | 5m-1=9 | | -10(s+5)=-72 | | –6+x=–3 | | _m-÷3=4 | | -6(3w-3)+2w=2(w+8) | | 2-x=9+2x | | -4(4x-2)+4x=9+3(2x-3) | | 3(2x+4)+2=-5x+25 | | 12-1,28(x-5)=22-2(x+4) | | 1+x/2-1/2-x/4+1/4=x/3+3/3 | | 3t+4=t13 | | 2x/4=x+3/3 | | 3x²=4x | | X²=2x | | 3z/10-4=3 | | (q-10)5=32 | | 5(q-10)=32 |

Equations solver categories